Wheels on the bus (The) - Ziefert, Harriet (New York : Random House, 1990)
The wheels on the bus go round, the wipers go swish, the doors open and cloes, and the people go in an out in this rollicking version of the classic song.
Keywords: Children's songs-Texts; Buses-Songs and music; Songs